Baicalein blocked cervical carcinoma cell proliferation by targeting CCND1 via Wnt/β-catenin signaling pathway. Issue 1 (4th December 2019) - Xia, Xiulian; Xia, Jiyi; Yang, Hai; Li, Yan; Liu, Shengyue; Cao, Yong; Tang, Li; Yu, Xiaolan
Abstract: The purpose of this study was to investigate the inhibitory effect of baicalein on the proliferation of cervical carcinoma cells and stimulate cervical carcinoma cells with baicalein. MTT method was used to observe cell proliferation. Flow cytometry was used to observe cell cycle, and gene technology was used to observe the expression of corresponding genes at the level of gene and protein. β-catenin activity was assessed using Western blot and ChIP. Baicalein suppressed cervical carcinoma cell HeLa proliferation by enhancing the activity of caspase-3. Baicalein blocked cell cycle at G0/G1 stage by inhibiting the expression of some genes. At the same time, it can prevent the nuclear translocation of β-catenin and inhibit the activity of Wnt. When the Wnt signaling pathway is increased, the proliferation of HeLa cells is inhibited, and apoptosis is promoted in this way. In conclusion, it indicated that baicalein inhibits cervical carcinoma progression by targeting CCND1 via Wnt/β-catenin signaling pathway.